Experimental study on the effect of sustained axial tension load at early age on the tensile strength of concrete during late splitting. Issue 7 (April 2020) - Zhuang, Jinping; Chen, Jianxing; Cai, Xuefeng; Qiu, Hao
Abstract: In order to study the effect of early-stage concrete loading on the tensile strength of the later splitting, a total of 7 series of specimens were designed. Through the sustained tension in early age, the effects of preloading axial tension ratio, loaded time and concrete strength on the tensile strength of concrete during splitting were discussed. A set of sustained tension device was set up by which six concrete specimens could be applied continuous pulling force together. The test results show that the sustained tension at early age has an adverse effect on the tensile strength of the late splitting. The reduction range is between 10.4% and 18.3% in the experimental parameters.